PERLINDUNGAN TERHADAP KEPENTINGAN PEREMPUAN DALAM PRAKTIK PERCERAIAN MUBARA’AH DI MASYARAKAT SASAK PULAU LOMBOK - Zulfatun Ni’mah (Muwazah, 2016)
this study aims to explore the reasons of women Sasak, preferring divorce mubara'ah ratherthan go through the legal procedures in courts and; mubara'ah divorce decision effectiveness in providing protection against the interests of women. The results showed that, women prefer to divorce mubara'ah Sasak village rather than litigation in court because it was easier, cheaper and faster than in court. overseas. The practice of mubara'ah be allowed to live by the government, and even tend to be protected, through the act of manipulating the data by the village government, in order that people who have divorced mubara'ah can remarry without having to show a divorce certificate from the court. The action manipulate this data, known, tolerated and accepted by the Office of Religious Affairs with the appropriate reason for divorce Islamic law. Divorce mubara'ah provides protection against the interests of women in society, related to marital status, the right to joint property and child custody. However, such protection is weak when dealing with the need of the orderly administration of the country, for example: birth certificate, family card, registration of Hajj and registration work abroad.Penelitian ini bertujuan untuk mengetahui alasan perempuan Sasak lebih memilih gugat cerai mubara’ah daripada menempuh prosedur hukum di pengadilan dan efektifitas putusan perceraian mubara’ah dalam memberikan perlindungan terhadap kepentingan perempuan. Hasil penelitian menunjukkan bahwa, perempuan Sasak lebih memilih perceraian mubara’ah di kampung daripada beracara di pengadilan karena lebih mudah, lebih murah dan lebih cepat dibanding di pengadilan. Praktik mubara’ah dibiarkan hidup oleh pemerintah, bahkan cenderung dilindungi melalui tindakan rekayasa data oleh pemerintah desa agar orang yang pernah bercerai secara mubara’ah dapat menikah lagi tanpa harus menunjukkan akta cerai dari pengadilan. Rekayasa data ini diketahui, dibiarkan dan diterima oleh Kantor Urusan Agama dengan alasan perceraian tersebut sesuai syariat Islam. Perceraian mubara’ah  memberikan perlindungan terhadap kepentingan perempuan di masyarakat, dalam bidang status perkawinan, hak harta bersama dan hak pengasuhan anak. Namun, perlindungan tersebut lemah ketika berhadapan dengan kepentingan tertib administrasi negara, misalnya: pembuatan akta kelahiran, Kartu Keluarga, pendaftaran haji dan pendaftaran kerja di luar negeri.